ANALISIS MODEL PROJECT BASED LEARNING TERHADAP KREATIVITAS SISWA PADA TEMA BENDA-BENDA DI SEKITAR KITA DI KELAS V SD NEGERI 067092 MEDAN - Ria Alda; Hasanah Hasanah (Sekolah Tinggi Pariwisata Mataram, 2023)
This study aims to analyze the Project Based Learning learning model on students' creativity on the theme of objects around us. This research was conducted at SD Negeri 067092 Medan. The method used in this study is a qualitative descriptive method. The instruments and data collection techniques used in this study were observation, interviews and documentation. In the initial observation, it was known that from 19 students in class V, there were only 5 students who had high creativity, while the other 14 students still had low creativity. The application of the Project Based Learning learning model on the theme of objects around us in class V, namely making jumputan batik. From the project implemented, the fifth grade students were very enthusiastic about participating in the learning process. Student creativity has also increased from before the Project Based Learning model was used. This can be seen from how students are able to make motifs on jumputan batik according to their respective creativity. After the Project Based Learning learning model made jumputan batik, from a total of 19 students in class V, 13 students had high creativity. Only 6 students tend to have low creativity. From this it can be said that the Project Based Learning learning model has a significant effect on the creativity of class V students